Systemic changes caused by artificial insemination in beef cows (Bos indicus) and their impact on animal welfare - Oliveira, Bruna Marcele Martins de; Arruda, Rubens Paes de; Maturana Filho, Milton; Birgel Júnior, Eduardo Harry; Birgel, Daniela Becker; Pogliani, Fábio Celidônio; Carneiro, Luisa Cunha; Celeghini, Eneiva Carla Carvalho (Brazilian Journal of Veterinary Research and Animal Science, 2021)
This study aimed to verify if the process of artificial insemination (AI) characterized here as animal immobilization, the passage of the semen applicator through the cervix, and deposition of the semen in the uterus, affected cows’ welfare. For this, 18 beef calved cows were selected and divided into two groups: inseminated cows (AIG, n = 9), and not inseminated cows, the control group (CG, n = 9). Body condition score, uterus, and ovary evaluation were performed. Later, both groups were submitted into an estrus synchronization protocol and only the AIG group was inseminated. Blood components of urea, creatinine, AST, GGT, CK, glucose, triglycerides, cholesterol, HDL, LDL, VLDL, NEFA, BHB, cortisol, estradiol, progesterone, albumin, and total protein were measured 30 h before AI, and 4, 24, 48 and 168 h after AI. Statistical differences were considered when P <0.05. No differences between AIG and CG were observed. On the other hand, when the moment of insemination was evaluated, differences were observed for urea, creatinine, AST, GGT, CK, glucose, triglycerides, NEFA, BHB, albumin, and total protein. There was an oscillation of metabolic profiles depending on the time and procedures to which animals were exposed, even though it could be inferred that the AI process was incapable of altering those metabolic components on animals that were inseminated. Still, we can affirm that artificial insemination cannot be categorized as a negative reproduction tool on animal welfare. However, the containment and management procedures for AI may alter the metabolic profile of cows, especially the increase of CK.